Pertimbangan Hukum Hakim Dalam Memutus Perkara Pemberian Keterangan Palsu Oleh Kepolisian (STUDI KASUS: PUTUSAN PENGADILAN NEGERI BANGKO No. 32 /Pid.B/2012/PN.BK.) - Kadarudin; Adi Wijaya; Mochamad Rifai (LPPM STIH Awang Long, 2021)
False information given by one of the police members based on the consideration of the judge based on the case study of the verdict of the case on behalf of the defendant Tamba Tua Sagala No. 32/Pid.B/2012/PN. bk. Bangko District Court, it becomes interesting to be studied analytically on the legal considerations given by judges to members of the judiciary who have committed violations of the law, because as it is known the police is one of the most important components in the criminal justice system against law enforcement. This research is a normative juridical law research. The technique used in this study is by inventorying primary legal materials, secondary legal materials, and tertiary legal materials, and this type of research uses a statute approach with data analysis methods using qualitative approaches.